Nitrobenzene poisoning presenting as Methemoglobinemia - Amit A Bharadiya; Akshay N Lakhotia; Aparna Patange; Jyotsna B Jaju; Kushal Choraria (Wolters Kluwer Medknow Publications, 2014)
Consumption of toxic compounds in an attempt to commit suicide is very common. Organophosphorus compounds are the most commonly consumed and fatal poisons. Nitrobenzene consumption for suicidal purposes is very rare. We would like to report a case of acute poisoning with nitrobenzene leading to methemoglobinemia, an unusual presentation.